Effects of phosphodiesterase (III/IV)-inhibitors and cytokines on mechanical properties of neutrophilic granulocytes in neonates and adults - Ruef, Peter; Craciun, Eugenia Maria; Altfelder, Jan Felix; Simon, Christoph; Frommhold, David; Koch, Lisa; Pöschl, Johannes (Clinical hemorheology and microcirculation, 2010)
Sequestration of activated PMN and enrichment in tissues play a key role in tissue damage during septicaemia and after ischemia/reperfusion. Since polymorphonuclear neutrophilic granulocytes (PMN) of term neonates show various functional differences
Gesehen am 22.06.2023
Selected Proceedings of the 15th Conference of the European Society for Clinical Hemorheology and Microcirculation (ESCHM), June 28–July 1, 2009, Pontresina, Switzerland